PERKEMBANGAN ANGKLUNG GUBRAG: DARI TRADISI RITUAL HINGGA HIBURAN (1983-2013) - Alin Novandini; Ayi Budi Santosa (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2017)
This article entitled “The Development of Angklung Gubrag from Ritual Tradition to Entertainment. The main problem of this article is how the development of Angklung Gubrag art in Kecamatan Cigudeg, Kabupaten Bogor since 1983-2013. This research has target to describe the backround of the beginning of Angklung Gubrag arts, the development of Angklung Gubrag arts, the efforts of artist do to converst this art, and the efforts of government to push and keep the art of Angklung Gubrag. The method which used in this research is historical method which consist of heuristic, critics, interpretation, and historiography. Angklung Gubrag is one of the art which comes from Kecamatan Cigudeg Kabupaten Bogor. Arts of Angklung Gubrag growth on society that has system of animism and dinamism. Firstly, it is shown as ritual media on the ceremony of Seren Taun which held to respect Nyi Pohaci. As tradisional arts, it was handed down from one generation to the other, and it has changing a lot. It is caused by changing of thinking society and their believed. After 1983, the artist who come from Padepokan Seni Angklung Gubrag change the tradition of Seren Taun. The purpose of this changed was to make society receive this art again. So that, the Angklung Gubrag art is also changing to be an entertainment. These development gives the changes in instrument, dance, and song to estetic of the Angklung Gubrag show. Beside the artist, the goverment is also act as supporter and protector of Angklung Gubrag art.